Diminished EEG habituation to novel events effectively classifies Parkinson's patients. Issue 2 (February 2018) - Cavanagh, James F.; Kumar, Praveen; Mueller, Andrea A.; Richardson, Sarah Pirio; Mueen, Abdullah
Highlights: Parkinson's patients do not show EEG habituation to novel events over time. This neural response classifies patients at 82% accuracy. These findings identify a systemic alteration that contributes to cognitive dysfunction. Abstract: Objectives: We aimed to test if EEG responses to novel events reliably dissociated individuals with Parkinson's disease and controls, and if this dissociation was sensitive and specific enough to be a candidate biomarker of cognitive dysfunction in Parkinson's disease. Methods: Participants included N  = 25 individuals with Parkinson's disease and an equal number of well-matched controls. EEG was recorded during a three-stimulus auditory oddball paradigm both ON and OFF medication. Results: While control participants showed reliable EEG habituation to novel events over time, individuals with Parkinson's did not. In the OFF condition, individual differences in habituation correlated with years since diagnosis. Pattern classifiers achieved high sensitivity and specificity in discriminating patients from controls, with a maximum accuracy of 82%. Most importantly, the confidence of the classifier was related to years since diagnosis, and this correlation increased as the time course of differential habituation increasingly distinguished the groups. Conclusions: These findings identify systemic alteration in an obligatory neural mechanism that may contribute to higher-level cognitive dysfunction in Parkinson's disease. Significance: These findings suggest that EEG responses to novel events in this rapid, simple, and inexpensive test have tremendous promise for tracking individual trajectories of cognitive dysfunction in Parkinson's disease.